Comparison of C-14 liquid scintillation counting at NIST and NRC Canada - Bergeron, Denis E. (Appl Radiat Isot, 2015)
An informal bilateral comparison of (14)C liquid scintillation (LS) counting at the National Research Council of Canada (NRC) and the National Institute of Standards and Technology (NIST) has been completed. Two solutions, one containing (14)C-labeled sodium benzoate and one containing (14)C-labeled n-hexadecane, were measured at both laboratories. Despite observed LS cocktail instabilities, the two laboratories achieved accord in their standardizations of both solutions. At the conclusion of the comparison, the beta spectrum used for efficiency calculations was identified as inadequate and the data were reanalyzed with different inputs, improving accord.